Plankton Biodiversity as an Indicator of the Health of the Estuary Ecosystem in Sinjai Regency, South Sulawesi - A Liswahyuni; Andi Tenriawaruwaty AR Zulkifli; Uspar Uspar; Irfan Fauzi; Ridha Alamsyah; Armita Permatasari (Poltanesa, 2026)
River estuaries are highly dynamic estuarine ecosystems. These ecosystems are sensitive to environmental changes, both caused by natural factors and human activities. Plankton community structure plays a crucial role as a biological indicator that reflects the ecological conditions and fertility levels of a body of water. This study aimed to analyze the diversity and abundance of plankton in five river estuaries in Sinjai Regency, including Lappa, Sinjai, Baringeng, Bua, and Pattongko Stations. This study also assessed the relationship between plankton presence and water physicochemical parameters. Sampling was conducted purposively, and plankton identification was performed microscopically. The results showed that 19 species of phytoplankton and 4 species of zooplankton were successfully identified. Diatoms dominated the phytoplankton species, such as Chaetoceros affinis, Nitzschia sigma, and Skeletonema costatum. The dominance of diatoms indicates water conditions ranging from mesotrophic to eutrophic, influenced by nutrient inputs in the form of nitrate and phosphate from land-based activities. The ANOVA test results showed no significant differences between stations (p > 0.05), indicating homogeneity of estuarine ecosystem conditions across all observation locations. Environmental parameters such as temperature (27–32°C), salinity (1–19 ppt), pH (6.1–7.8), high dissolved oxygen, and nutrient variations also play a role in plankton distribution. These findings provide important baseline information for estuarine ecosystem monitoring and sustainable coastal area management based on bioindicators in Sinjai Regency.